The Alchemist - Jonson, Ben 1572-1637 (Arden early modern drama, 2023)
A fast-paced whirlwind of fantasy and mockery confined to a single room, The Alchemist offers a witty culmination of Jonson's experiments with city comedy. The play has been widely recognized as one of the most impressive achievements of the period's theatre; Coleridge famously described it as one of the three most perfect plots in literature. Yet it is a notoriously difficult play: its alchemical language has aged into obscurity, and its insiderly humour can seem impenetrable to students approaching it for the first time. This comprehensively annotated edition translates and illuminates the play's many pleasures and shows how Jonson's cynical, street-wise wit resonates with our contemporary sensibilities. Pollard highlights the play's witty ingenuity, while offering the information and guidance to enable students to understand and enjoy The Alchemist fully